Evidence for wind-induced Ekman layer resonance based on rotating tank experiments. (13th March 2019) - Vincze, M.; Fenyvesi, N.; Klein, M.; Sommeria, J.; Viboud, S.; Ashkenazy, Y.
Abstract: The temporal variability of wind stress acting on the ocean surface may have a significant impact on the energy transfer between the surface ocean and the abyssal ocean. In particular, the surface ocean layer is expected to deepen when the wind's frequency matches the inertial (Coriolis) frequency, through "Ekman layer resonance". Here, we report on laboratory experiments conducted in the large circular rotating tank of the LEGI Coriolis platform (13 m in diameter and 0.5 m in depth) to investigate the effect of oscillating horizontal shear imposed at the water surface. The analysis of the flow structure by means of particle image velocimetry (PIV) reveals a resonant thickening of the top Ekman layer and a marked increase in the kinetic energy of the flow occurs when the forcing frequency coincides with the Coriolis frequency of the rotating tank. The findings are in agreement with the theoretical expectations and constitute evidence for the existence of the Ekman layer resonance (or near inertial resonance) phenomenon in an ocean-like configuration.